2013
DOI: 10.1038/emboj.2013.32
|View full text |Cite
|
Sign up to set email alerts
|

NDR2-mediated Rabin8 phosphorylation is crucial for ciliogenesis by switching binding specificity from phosphatidylserine to Sec15

Abstract: Primary cilia are antenna-like sensory organelles protruding from the plasma membrane. Defects in ciliogenesis cause diverse genetic disorders. NDR2 was identified as the causal gene for a canine ciliopathy, early retinal degeneration, but its role in ciliogenesis remains unknown. Ciliary membranes are generated by transport and fusion of Golgi-derived vesicles to the pericentrosome, a process requiring Rab11-mediated recruitment of Rabin8, a GDP-GTP exchange factor (GEF) for Rab8, and subsequent Rab8 activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 47 publications
5
98
0
Order By: Relevance
“…Rabin8, the homolog of Sec2p, is recruited to the pericentrosome at the base of the cilia by binding to Rab11 (10), the homolog of Ypt32p, but it also binds to the mammalian homolog of Sec15p. Interestingly, phosphorylation of Rabin8 at S272, a site that aligns with the 181-188 region of Sec2p, promotes binding to Sec15p and inhibits binding to Rab11 (16), exactly paralleling the regulation we report here. Although Rabin8 does not bind to PI(4)P, as does Sec2p, it does bind to phosphatidylserine, and this affinity is reduced by phosphorylation, just as the affinity of Sec2p for PI(4)P is reduced by phosphorylation (16).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Rabin8, the homolog of Sec2p, is recruited to the pericentrosome at the base of the cilia by binding to Rab11 (10), the homolog of Ypt32p, but it also binds to the mammalian homolog of Sec15p. Interestingly, phosphorylation of Rabin8 at S272, a site that aligns with the 181-188 region of Sec2p, promotes binding to Sec15p and inhibits binding to Rab11 (16), exactly paralleling the regulation we report here. Although Rabin8 does not bind to PI(4)P, as does Sec2p, it does bind to phosphatidylserine, and this affinity is reduced by phosphorylation, just as the affinity of Sec2p for PI(4)P is reduced by phosphorylation (16).…”
Section: Discussionsupporting
confidence: 54%
“…Phosphorylation of Rabin8 at serine 272 is directed by the NDR2 kinase (16,17). The yeast NDR kinase, Cbk1, binds to Sec2p and will phosphorylate Sec2p in vitro (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDR2 phosphorylation was implicated in primary ciliogenesis in mammalian cells (36). In flies, this phosphorylation event was shown to be important for dendrite arborization (37).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study focuses on the effect of ERK1/2 on the activation of Rabin8, previous studies have shown the phosphorylation of Rabin8 by NDR2 at a different site, S272 (36). NDR2 phosphorylation was implicated in primary ciliogenesis in mammalian cells (36).…”
Section: Discussionmentioning
confidence: 99%